Disfemismo e eufemismo: o desmatamento da Amazônia em artigos de opinião na mídia brasileira e americana: um enfoque sistêmico-funcional - Cardoso, Amanda Silva (2020)
Politicians and speakers use words as weapons to exert ideological control and ostensibly make the audience believe their words. In this regard, considering critical analysis of political discourse based on theoretical persuasion resources, the objective of this master's dissertation is to examine the persuasive use of dysphemistic or euphemistic words and expressions based on the Conceptual Metaphor Theory in two opinion articles on deforestation in the Amazon, one published in Folha de S.Paulo newspaper and another in The New York Times, on the same date (18.11.2019). Dysphemism is a figure of speech that, in opposition to euphemism, consists in the deliberate use of derogatory, sarcastic or foul terms or expressions to refer to a certain theme, thing or person. The analysis of opinion articles also uses the theory of conceptual metaphor, taking into account the fact that conceptual metaphors are the result of interaction with conceptual metonymy, which provides contiguity between the text and the reader frame. As for the contribution to the persuasive process that runs through the two opinion articles, the analysis relies on the notions of voicing, reported speech and legitimation. Methodologically, these resources will be examined in the light of Critical Linguistics, relying on Systemic-Functional Linguistics (including modality and appraisal), to show that the interpretations given by the two newspapers are built by specific choices in the microstructure of the text, revealing ideologies in the macrostructure of speech. This survey answers the following questions: (a) what role do dysphemism and euphemism play concerning persuasion that goes through opinion articles analyzed? (b) what is the role of metaphors found in the discourse of the articles? (c) what rhetorical resources do the opinion articles under analysis use in order to persuade the readers? The results show that dysphemism can be considered a delegitimization technique, through which politicians are presented negatively to make people support a cause or promote public morals, while euphemism tends to criticize implicitly